Kippe em hastes retas em regime elasto-plástico - Costa, Eliane Derani da (1983)
The object of the present thesis is an investigation of the problem of elasto-plastic lateral buckling of beams. The theory is based on the general formulation of elastic stability due to G. H. Bryan. The buckling equations are solved by the method of finite differences, both in the elastic and the elasto-plastic range. Relevant results are discussed in a special chapter. In order to avoid, more involved questions, numerical treatments have been restricted to steel beams with rectangular cross-section.